Efeito antimicrobiano do ozônio no processamento da tilápia do nilo, Oreochromis niloticus (Linnaeus, 1758) - Silva, Andressa Medeiros de Mendonça (Universidade Federal Rural do Semi-Árido, 2015)
The objective of this study was to evaluate the efficiency of ozonated water as an antimicrobial agent in the Nile tilapia (O. niloticus) processing. Samples of whole tilapia and fillets were washed with cold water (11 ° C), without ozone (0 ppm - control) and with ozone (0.5; 1.0; 1.5 ppm) for 0; 5; 10; and 15 minutes. Microbiological parameters (total count of mesophilic, Staphylococcus aureus positive coagulase counts, fecal coliforms and the presence of Salmonella sp.) and physicochemical parameters (pH, color, TBA) were evaluated in order to check the microbiological load reduction and possible changes on pH, color and lipid oxidation (TBA) of fillets. The most effective ozone concentration on reducing the microbial load of the surface of tilapia was 1.5 ppm, reducing the initial populations of mesophilic bacteria in 91.78%. At this concentration (1.5 ppm), it was effective within the first 5 min., reducing the microbial load of 71.23%. In fillet washing, 1.5 ppm ozone concentration also showed the greatest reduction of mesophilic bacteria 70.19%. The treatment with ozonated water of fillets showed no influence on the pH and color of the fillets, however, there was an increase in the TBA value (1.5 ppm of O3 for 15 min.), showing that lipid oxidation occurred, but below the thresholds that make them unfit for consumption. The results showed that the ozonated water has been effective in reducing the microbial load of the fish during processing. The cost of electricity consumption used for ozone generation demonstrated its feasibility of use
Antimicrobial effect of ozone in the Nile tilapia, Oreochromis niloticus (Linnaeus, 1758) processing
Keywords: Agente oxidante; Água ozonizada; Pescado; Qualidade; Segurança alimentar; Oxidant agent; Ozonized water; Seafood; Quality; Food Safety; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL